DESKRIPSI KESALAHAN PENAMAAN SENYAWA ANORGANIK DAN ORGANIK SEDERHANA SISWA KELAS X TEKNIK PEMESINAN SMK-SMTI PONTIANAK - Arridho, Bob; Melati, Husna Amalya; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe background of this research are low result of students achievement in studying and there were still many students who have difficulty in material of simple inorganic and organic compound nomenclature. The aims of this research are to investigate  error and to determine that cause of students? errors of mechanical engineering SMK-SMTI Pontianak. The method of this research is descriptive study. As many as 28 students of XC participate on this research. Essay tests and free guides interview are used to collect the data. Based on the result, It could be known that the students? error in understanding of essential concept is lack of understanding several concepts of : element symbol, element name, element location in group, symbol and name of ion, charge or oxidation number, differentiating between elements and poliatomic ions, and name of compound. The students? error in understanding use of concepts to solve problem are : error in using concept of writing name of compound, and error in using concept of writing chemistry formula. The causes of students? error are students had difficully in remembering concept and managing time to study, forget the prerequiresite concept, and had lack of carefulness in reading and finishing the test.Keywords: Description, Error, Cause of Error, simple inorganic and organic compound nomenclature